2006
DOI: 10.1021/ic052189r
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Single-Crystal Ce(OH)CO3and CeO2Triangular Microplates

Abstract: Single-crystal cerium hydroxide carbonate (Ce(OH)CO3) triangular microplates with the hexagonal phase have been successfully synthesized by a hydrothermal method at 150 degrees C using cerium nitrate (Ce(NO3)3.6H2O) as the cerium source, aqueous carbamide as both an alkaline and carbon source, and cetyltrimethylammonium bromide (CTAB) as a surfactant. Single-crystal ceria (CeO2) triangular microplates have been fabricated by a thermal decomposition-oxidation process at 650 degrees C for 7 h using single-crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 24 publications
2
66
1
Order By: Relevance
“…The major weight loss occurred at 440-640 8C, which was due to decomposition of CeCO 3 OH precursors. The total weight loss was calculated at 23.59%, which was consistent with the theoretical weight loss results of the following reactions: [52] 4CeCO 3 OH + O 2 !4CeO 2 + 4CO 2 + 2H 2 O. The maximum endothermic peak at 462 8C and a small endothermic peak at 550 8C indicated that the thermal decomposition of CeCO 3 OH precursors to CeO 2 was the endothermic process.…”
Section: Hr-temsupporting
confidence: 86%
“…The major weight loss occurred at 440-640 8C, which was due to decomposition of CeCO 3 OH precursors. The total weight loss was calculated at 23.59%, which was consistent with the theoretical weight loss results of the following reactions: [52] 4CeCO 3 OH + O 2 !4CeO 2 + 4CO 2 + 2H 2 O. The maximum endothermic peak at 462 8C and a small endothermic peak at 550 8C indicated that the thermal decomposition of CeCO 3 OH precursors to CeO 2 was the endothermic process.…”
Section: Hr-temsupporting
confidence: 86%
“…Structure and morphology In spite of previous report that urea and Ce 3+ favors forming CeOHCO 3 under hydrothermal treatment [11,12], our group has demonstrated that CeO 2 hollow spheres were formed using urea as precipitator in the presence of H 2 O 2 [6]. In order to make the size of nanocrystals in the CeO 2 sub-microspheres controllable, we change the amount of CO(NH 2 ) 2 because of its slow hydrolysis kinetics in the hydrothermal surroundings.…”
Section: Resultsmentioning
confidence: 98%
“…A 2Si(OH) 4 is used as a hydrolysis zone and separated to the polymerize coating in the form of a range which is held by pH = 11. And then, oxides of Si single molecules then cover the surface of the nano-compounds [14,15].…”
Section: Resultsmentioning
confidence: 99%